Nootropic herbs (Medhya Rasayana) in Ayurveda: An update - Kulkarni, Reena; K. J, Girish; Kumar, Abhimanyu (Pharmacognosy Reviews, 2012)
Cognitive defi cits that present with many of neuropsychiatric conditions and/or alone as developmental defi cit demand use of nootropics to boost cognitive abilities. Recently there is a tremendous urge to explore medicinal plants globally for improving cognitive function owing to their less adverse effects. Ayurveda provides a list of herbs known for nootropic activity as well as their multi-dimensional utility in various conditions. Present paper is a review to update knowledge on pharmacological properties, major chemical constituents, therapeutic actions, preclinical studies, safety and possible mode of action of the selected herbs from ayurvedic pharmacopoeia. Concurrently, it opens up for further research and standardization on nootropic herbs
Keywords: Ayurveda; memory enhancer; Medhya Rasayana; nootropic